The Influence of the Contextual Teaching and Learning (CTL) Model on Learning Outcomes of Class IV Style Material - Fransiska, Dwi Cherry; Rahmi, Laili (Universitas Negeri Semarang, 2024)
To get successful learning outcomes in science subjects in fourth grade elementary school material, teachers must use the right learning model. The aim of this research is to find out how much influence the contextual teaching and learning (CTL) model has on student learning outcomes in class IV style material at SDN 131 Pekanbaru. This research uses a quantitative approach with quasi-experimental research methods (quasi-experiments). The population in this study was 40 students with a sample of 20 students from class IV A as the experimental class and 20 students from class IV B as control class students. Sample selection is based on a partial population. The instrument used in this research was a test sheet to measure the abilities of class IV students at SDN 131 Pekanbaru. The analysis techniques used are descriptive analysis and inferential analysis. This test is used to see the influence or not of the contextual teaching learning (CTL) learning model. The results of the research show that there is an influence on the use of the CTL learning model on the learning outcomes of style material in class IV SDN 131 Pekanbaru. This is proven by the results of hypothesis testing using the t-test, obtained